Free Expression, Globalism, and the New Strategic Communication - Price, Monroe E., 1938- (New York : Cambridge University Press, 2015)
"Exposes the anxieties of loss of control and missed opportunities for greater freedom of expression resulting from changes in technologies and geopolitics."--
"Vast changes in technologies and geopolitics have produced a wholesale shift in the way states and other powerful entities think about the production and retention of popular loyalties. Strategic communication has embraced these changes as stakes increase and the techniques of information management become more pervasive."--
1. Moving the needle, filling the streets; 2. Strategic communication and the foundations of free expression; 3. Narratives of legitimacy; 4. Strategies of the diagnostic; 5. Asymmetries and strategic communication; 6. Strategies of system architecture; 7. Soft power, soft war; 8. Religions and strategic communication; 9. Regulating NGOs in the market for loyalties; 10. Strategic platforms; 11. Strategic communication and satellite channels; 12. Strategies of closure, marker of anxiety.
Includes bibliographical references (p. 255-267) and index.
Keywords: Freedom of expression; Telecommunication -- Law and legislation; Globalization; Geopolitics